Probing longitudinal modes evolution of a InGaN green laser diode. (June 2018) - Chen, Yi-Hsi; Lin, Wei-Chen; Chen, Hong-Zui; Shy, Jow-Tsong; Chui, Hsiang-Chen
Abstract: This study aims to investigate the longitudinal mode evolution of a InGaN green laser diode. A spectrometer with a 3-pm resolution was employed to obtain the emission spectra of a green laser diode, at a wavelength of around 520 nm, as a function of applied current and temperature. The spectral behavior of the laser modes with applied current was investigated. Right above the lasing threshold, the green diode laser emitted single longitudinal mode output. With increasing applied current, the number of the longitudinal modes increased. Up to ten lasing modes oscillated within the entire gain profile when the applied currents were tuned to 2.2Ith . Subsequently, a multi-Lorentzian profile model was adopted to analyze the spectra and observe how the modes evolved with temperature and applied current.